Forest multifunctionality is not resilient to intensive forestry - Pohjanmies, Tähti; Eyvindson, Kyle; Triviño, María; Bengtsson, Jan; Mönkkönen, Mikko (Springer, 2021)
There is ample evidence that intensive management of ecosystems causes declines in biodiversity as well as in multiple ecosystem services, i.e., in multifunctionality. However, less is known about the permanence and reversibility of these responses. To gain insight into whether multifunctionality can be sustained under intensive management, we developed a framework building on the concept of resilience: a system’s ability to avoid displacement and to return or transform to a desired state. We applied it to test the ability of forest multifunctionality to persist during and recover from intensive management for timber production in a boreal forest. Using forest growth simulations and multiobjective optimization, we created alternative future paths where the forest was managed for maximal timber production, for forest multifunctionality, or first maximal timber production and then multifunctionality. We show that forest multifunctionality is substantially diminished under intensive forestry and recovers the slower, the longer intensive forestry has been continued. Intensive forestry thus not only reduces forest multifunctionality but hinders its recovery should management goals change, i.e., weakens its resilience. The results suggest a need to adjust ecosystem management according to long-term sustainability goals already today.
Keywords: Sustainable forest management; ecosystem services; Biodiversity; Boreal forest; Finland; Transformation capacity